Neoadjuvant immunochemotherapy versus chemotherapy for elderly patients with IB–IIIB non-small-cell lung cancer in real-world practice - Yongfeng Shuai; Jiacong Liu; Yuhong Yang; Xuhua Huang; Jiayue Ye; Linhai Zhu; Jian Hu (BMC Cancer)
Abstract Background Immunochemotherapy is currently the standard treatment plan for non-small-cell lung cancer (NSCLC) patients with no driver gene mutations. However, it is uncertain whether immunochemotherapy is effective or safe for elderly patients (≥ 65 years). Therefore, this study compared preoperative immunochemotherapy and chemotherapy with stage IB-IIIB NSCLC in elderly patients (≥ 65 years) for safety and effectiveness. Methods Between 2016 and 2022, all elderly patients (≥ 65 years) with IB–IIIB NSCLC who underwent 2–4 cycles of neoadjuvant immunochemotherapy or chemotherapy at the Department of Thoracic Surgery, the First Affiliated Hospital, Zhejiang University School of Medicine were consecutively included in this retrospective study. In this study, we followed up patients for at least 1 year after surgery or until they abandoned treatment. The primary endpoints of this study were disease-free survival (DFS) and overall survival (OS). The secondary endpoints were composed of pathological response [major pathological response (MPR) and pathological complete remission (pCR)], adverse events (AEs) and objective response rate (ORR). Results We included 140 patients in our study and classified them into two groups according to their neoadjuvant treatment regimen: chemotherapy (n = 47) and immunochemotherapy (n = 93). In the chemotherapy group, the median DFS was 19.4 months [95% confidence interval [CI], 2.4 to 36.4], but not achieved by the immunochemotherapy group (hazard ratio [HR] for disease progression, disease recurrence, or death, 0.247; 95% CI, 0.122 to 0.501; P < 0.001). The chemotherapy group had a median OS of 41.8 months (95% CI, 9.1 to 74.5), while the median OS of the immunochemotherapy group was not achieved (HR for death,0.265; 95% CI, 0.115 to 0.611; P < 0.001). The immunochemotherapy group had a significantly higher ORR than the chemotherapy group (73.1% vs. 29.8%, P < 0.001). The immunochemotherapy group had 19.4% of grade 3–4 AEs, while the chemotherapy group had 8.5% (P = 0.156). The immunochemotherapy group showed a significantly higher rate of MPR than the chemotherapy group (64.4% vs. 25.8%, P < 0.001). The immunochemotherapy group had a pCR rate of 32.2%, while the chemotherapy group had a pCR rate of 16.1% (P = 0.101). Conclusions Neoadjuvant immunochemotherapy was associated with improved survival rates, ORR, and MPR rates compared to chemotherapy alone in elderly patients (≥ 65 years) with IB-IIIB NSCLC, without a significant increase in AEs.